2020
DOI: 10.1155/2020/3428945
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Inhibitor Therapy in a Patient with Preexisting P-ANCA Vasculitis: A Case Report and Review of the Literature

Abstract: Background. Recurrent endometrial cancer after definitive therapy is a lethal disease. Recently, immune checkpoint inhibitors (ICI) have improved the management of mismatch repair-deficient (MSI-H) endometrial cancer. Autoimmune side effects are known to occur with ICI. As a result, patients with preexisting autoimmune diseases are excluded from studies involving these drugs. This has led to challenges in clinical practice regarding the use of ICI in otherwise eligible patients with underlying autoimmune disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The search strategy retrieved 72 articles. Overall, 18 reviews (21-38) and 8 case reports (39)(40)(41)(42)(43)(44)(45)(46) were identified, while 40 studies were deemed irrelevant. After removal of ineligible studies, 6 studies were recruited (47)(48)(49)(50)(51)(52).…”
Section: Data On Efficacy and Safetymentioning
confidence: 99%
“…The search strategy retrieved 72 articles. Overall, 18 reviews (21-38) and 8 case reports (39)(40)(41)(42)(43)(44)(45)(46) were identified, while 40 studies were deemed irrelevant. After removal of ineligible studies, 6 studies were recruited (47)(48)(49)(50)(51)(52).…”
Section: Data On Efficacy and Safetymentioning
confidence: 99%